Perinatal outcome and prognostic factors of fetal megacystis diagnosed at 11–14 week's gestation. (30th November 2020) - Kao, Cindy; Lauzon, Julie; Brundler, Marie‐Anne; Tang, Selphee; Somerset, David
Abstract: Objectives: To evaluate aneuploidy rate, prognostic factors, and perinatal outcomes following a diagnosis of fetal megacystis at 11–14 week's gestation. Methods: A retrospective study of first trimester fetal megacystis from 2010 to 2020 was performed, including ultrasound finding, perinatal outcomes, pathology reports, genetic tests, and neonatal investigations. Results: A total of 98 cases of first trimester fetal megacystis was identified with an overall aneuploidy rate of 12%. There were 54% live births and 46% fetal losses including spontaneous fetal demise and elective termination. Among the 45 fetal losses, 64% had additional structural abnormalities at index ultrasound and final diagnoses were achievable in 64% cases. Among the 53 livebirths, additional ultrasound abnormalities were detected in only 1 fetus and spontaneous resolution of megacystis was detected in 96% of cases. The two cases where fetal megacystis persisted had major postnatal diagnoses: cloacal malformation and megacystis‐microcolon‐intestinal hypoperistalsis syndrome, respectively. Our data showed LBD ≥ 12 mm was the best individual predictor of adverse perinatal outcome and all 11 cases of lower urinary tract obstruction (LUTO) were diagnosed in fetuses with LBD ≥ 12 mm. Conclusions: First trimester ultrasound provides important prognostic factors and isolated megacystis <12 mm is associated with a positive outcome.